PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MINAT BELAJAR SISWA - Yoseptry, Ricky; Nurihayati, Emilya; Setiani, Erna Erawati; Silviana, Karisma; Muharisa, Dini (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This research aims to determine the effect of using interactive learning media in increasing students' interest in learning at SDN Giriwinaya. The purpose of the study is to describe the effect of using interactive learning media in increasing students' interest in learning at SDN Giriwinaya. This research method uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The research participants consisted of fourth grade students, teachers, and principals. The results of the study showed that the use of interactive learning media, such as educational games, learning videos, and interactive applications, was able to significantly increase students' interest in learning. Students became more active, enthusiastic, and involved in the learning process, because the learning process became more interesting and enjoyable. In addition, teachers also felt an increase in the effectiveness of teaching with this interactive media. Supporting factors found include the provision of adequate technological facilities and teacher training in the use of interactive media. However, there are challenges such as limited internet access and the technical skills of some teachers that need to be improved. The conclusion of this study is that interactive learning media is an effective tool in increasing students' interest in learning at SDN Giriwinaya, provided that there is adequate infrastructure support and training. This study recommends increasing access to technology and developing teacher competencies as further steps to strengthen the implementation of interactive learning media in elementary schools.